Assessing the Effectiveness of Telepharmacy Services in Rural and Underserved Areas (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study evaluates the effectiveness of telepharmacy services in improving healthcare delivery in rural and underserved areas. Utilizing a mixed-methods design, both quantitative and qualitative data were collected over a 12-month period. The study involved 200 patients who used telepharmacy services, providing remote access to pharmacists for medication dispensing, consultations, and patient education. Quantitative data included patient surveys on medication adherence and satisfaction, along with medication records to assess dispensing errors. Qualitative data were obtained through interviews with patients and pharmacists to explore their experiences.Results indicated a significant increase in medication adherence rates from 60.0% to 85.0% post-telepharmacy implementation. Patient satisfaction scores across various domains improved notably, with mean scores for access to pharmacists, quality of consultations, and overall satisfaction showing significant enhancements (p < 0.001). Additionally, there was a substantial reduction in medication errors, with dispensing errors decreasing from 15.0% to 5.0% (p < 0.01) and prescription errors from 10.0% to 4.0% (p < 0.05). Economic analysis revealed a decrease in healthcare costs per patient from $2000 to $1500, along with a reduction in hospitalizations per 1000 patients from 50 to 30 (p < 0.01).These findings are consistent with previous studies and underscore the potential of telepharmacy as a cost-effective and efficient solution to healthcare disparities in rural and underserved regions. Despite technological and regulatory challenges, telepharmacy represents a promising approach to enhancing healthcare access, improving clinical outcomes, and achieving significant cost savings in rural healthcare systems.